A construction and comprehensive analysis of the immune-related core ceRNA network and infiltrating immune cells in peripheral arterial occlusive disease - Chen, Zhiyong; Xu, Jiahui; Zha, Binshan; Li, Jun; Li, Yongxiang; Ouyang, Huan (Frontiers in Genetics, 2022)
Background: Peripheral arterial occlusive disease (PAOD) is a peripheral artery disorder increasing with age, and often leads to an elevated risk of cardiovascular events. The purposes of this study were to explore the underlying competing endogenous RNA (ceRNA)-related mechanism of PAOD and identify the corresponding immune cells infiltration patterns. Methods: An available gene expression profile (GSE57691 datasets) was downloaded from the GEO database. Differentially expressed (DE) mRNAs and lncRNAs were screened between 9 PAOD and 10 control samples. Then the lncRNA-miRNA-mRNA ceRNA network was constructed on the basis of the interaction generated from the miRcode, TargetScan, miRDB, and miRTarBase databases. The functional enrichment and protein-protein interaction analysis of mRNAs in ceRNA network were performed. Immune-related core mRNAs were screed out through Venn method. The compositional patterns of the 22 types of immune cell fraction in PAOD were estimated through CIBERSORT algorithm. The final ceRNA network and immune infiltration were validated using clinical tissue samples. Finally, the correlation between immune cells and mRNAs in the final ceRNA network was analyzed. Results: Totally, 67 DE_lncRNAs and 1197 DE_mRNAs were identified, in which 130 DE_mRNAs (91 down-regulated and 39 up-regulated) were lncRNA-related. The gene ontology enrichment analysis showed that those down- and up-regulated genes were involved in dephosphorylation and regulation of translation, respectively. The final immune-related core ceRNA network included 1 lncRNA (LINC00221), 2 miRNAs (miR-17-5p and miR-20b-5p), and 1 mRNA (CREB1). Meanwhile, we found that monocytes and M1 macrophages were the main immune cell subpopulations in PAOD. After verification, these predictions were consistent with experimental results. Moreover, CREB1 was positively correlated with naive B cells (R = 0.55, p = 0.035) and monocytes (R = 0.52, p = 0.049) and negatively correlated with M1 macrophages (R = −0.72, p = 0.004), resting mast cells (R = −0.66, p = 0.009), memory B cells (R = −0.55, p = 0.035), and plasma cells (R = −0.52, p = 0.047). Conclusion: In general, we proposed that the immune-related core ceRNA network (LINC00221, miR-17-5p, miR-20b-5p, and CREB1) and infiltrating immune cells (monocytes and M1 macrophages) could help further explore the molecular mechanisms of PAOD.